Предмет: Алгебра,
автор: miraaa
помогите!!lРешить ур-ие lg(х-2)+lg(х-3)=1-lg5
Ответы
Автор ответа:
0
Ответ 1 и 4.
lg(x-2)(x-3)=1-lg5
lg(x-2)(x-3)+lg5=1
lg5(x-2)(x-3)=1
5(x-2)(x-3)=10
(x-2)(x-3)=2
x2-5x+6=2
x2-5x+4=0
(x-4)(x-1)=0
x=1
x=4
Автор ответа:
0
ОДЗ: x>3
lg(x-2)+lg(x-3)=lg10-lg5
lg((x-2)*x-3))=lg2 ОДЗ: x>3 и x<2, но 1е ОДЗ строже, поэтому х>3
(х-2)*(х-3)=2
х:2-5х+4=0
х=1 - не подходит по ОДЗ
х=4 подходит.
Ответ: х=4
Будьте внимательнее.
Похожие вопросы
Предмет: Физика,
автор: kushniranastasia2007
Предмет: Математика,
автор: Аноним
Предмет: Английский язык,
автор: petrovanastya505
Предмет: Литература,
автор: 270397